STRESSES IN SYIMMETRICALLY LOADED STEPPED CIRCULAR PLATES USING FINITE ELEMENT METHOD - Shebl, M. G.; Uj, J. (Periodica Polytechnica Mechanical Engineering, 1989)
This paper deals with theoretical and numerical investigations for the stresses induced incircular plates with variable thickness and exposed by static loads. The effects of different types ofloads on stresses are considered. The radial and hoop stresses are obtained for stepped circularplates widely used in industry. Two different forms of such plates are considered, one has a raisedcentral region and the other has an unraised one. The results are obtained by finite element methodusing a tapered annulus bending element. The graphs presented in this work show the effect of thedifferent values of step radius, type of the applied load and the effect of the different boundary conditionson the stresses from the point of view of design. When the step radius vanishes or equals tothe plate radius, the plate becomes of uniform thickness. Consequently, the results obtained can becompared with the values of exact solutions. The limits of this simple finite element model for steppedplates are investigated by a more advanced finite element model having three dimensional axisymmetricannular element.